ANALYSIS THE CONTRIBUTION OF LAND AND BUILDING TAX AND ACQUISITION OF LAND AND BUILDING RIGHTS ON LOCAL REVENUE IN KUBU RAYA REGENCY - B1034141010, FIRNA FIRYANTI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ABSTRACTThis research have several objectives which are to analyze the contribution of Land and Building Tax (PBB) and Acquisition of Land and Building Rights (BPHTB) to Local Revenue (PAD); to analyze the level of effectiveness of PBB and BPHTB and to investigate the ways that government set the targets of taxes on PBB and BPHTB as well as to find out the factors that might influence the low acceptance of PBB in Kubu Raya Regency.Furthermore, the source of data that used in this study is derived from the primary and secondary data. Primary data comes from interviews which conducted by researchers while secondary data got by studying documents, articles and journals. Not only that, the data which used was taken from 2012 until 2016. Furthermore, the method used in this research is qualitative method with case study approach.The result of this research is known that the contribution of PBB in Kubu Raya Regency is very low because it only reaches 9.43%, while for the contribution of BPHTB in Kubu Raya regency is included in low category which is only got 35.23%. Then, for the effectiveness of PBB, it included in the category of less effective and reached 75.53% while BPHTB got effective category because it reached until 91.95%. The determination of PBB and BPHTB targets in Kubu Raya Regency is done by executive and legislative parties. After that, both of parties will conduct deliberation to get the appropriate target nominal and will be submitted to the province to become APBD. In addition, there are some factors that affect the low acceptance of PBB in Kubu Raya regency, namely: low public awareness to pay taxes; inadequate facilities and infrastructure; there is still no enforcement of strict rules for people who do not pay taxes; require more routine socialization; unidentified tax subjects and soon.Keywords: Contribution, Effectiveness, Target Determination, PBB, BPHTB.